2018
DOI: 10.1080/21501203.2018.1448009
|View full text |Cite
|
Sign up to set email alerts
|

Do volatile compounds produced by Fusarium oxysporum and Verticillium dahliae affect stress tolerance in plants?

Abstract: Volatile compounds (VCs) produced by diverse microbes seem to affect plant growth, development and/or stress tolerance. We investigated how VCs released by soilborne fungi Fusarium oxysporum and Verticillium dahliae affect Arabidopsis thaliana responses to abiotic and biotic stresses. Under salt stress, VCs from both fungi helped its growth and increased chlorophyll content. However, in contrast to wild-type A. thaliana (Col-0), V. dahliae VCs failed to increase leaf surface area in auxin signalling mutants au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…To prevent physical contact and exposure to secreted molecules diffused through medium while studying how VCs from each side affect the other, we initially evaluated I plate. This plate contains two compartments separated by a central divider and has been used for studying how fungal VCs affect plants (Bitas et al, 2015 ; Li and Kang, 2018 ; Li et al, 2018 ). However, because Trichoderma jumped over the divider even after we removed a strip of medium along the divider in both compartments, we used a method reported by Dennis and Webster ( 1971 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent physical contact and exposure to secreted molecules diffused through medium while studying how VCs from each side affect the other, we initially evaluated I plate. This plate contains two compartments separated by a central divider and has been used for studying how fungal VCs affect plants (Bitas et al, 2015 ; Li and Kang, 2018 ; Li et al, 2018 ). However, because Trichoderma jumped over the divider even after we removed a strip of medium along the divider in both compartments, we used a method reported by Dennis and Webster ( 1971 ).…”
Section: Resultsmentioning
confidence: 99%
“…Plant VCs function as homing cues to pollinators, seed dispersers, and parasitoids (Baldwin, 2010 ; Herrmann, 2010 ), mediate communication within and between plants (Baldwin, 2010 ), and protect plants from diverse predators (Baldwin, 2010 ; Huang et al, 2012 ; Arasimowicz-Jelonek and Floryszak-Wieczorek, 2014 ). Similarly, microbial VCs appear to participate in microbial interactions (Bailly and Weisskopf, 2012 ; Bennett et al, 2012 ; Bitas et al, 2013 ) and also affect plant growth, development, and stress resistance (Bailly and Weisskopf, 2012 ; Bitas et al, 2013 ; Li et al, 2016 ; Li and Kang, 2018 ). VCs produced by biocontrol agent Paenibacillus polymyxa and soilborne fungal pathogen Verticillium longisporum appeared to affect the production of antimicrobial VCs and other metabolites in the other side (Rybakova et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In present study, we found most stress response genes were down-regulated during domestication, and this is responsible for the decreased stress tolerance of upland cotton ( Figure 5 ). PR1 gene is a useful molecular marker for the salicylic acid (SA) response and has been reported to play crucial roles in systemic acquired resistance in Arabidopsis (Li and Kang, 2018). VIGS assay showed that silencing of PR1 significantly reduced the disease resistance of cotton ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Pseudomonas aeruginosa and Bacillus anthracis are associated with a number of human diseases (Forni et al, 2017), yet they produce high levels of compounds such as ACC deaminase. The fungus Fusarium oxysporum is a pathogen of many crop species, yet it produces VOCs that mitigated salinity stress effects in the model plant Arabidopsis thaliana, increasing chlorophyll content and leaf area (Li and Kanga, 2018). In such cases, isolating compounds in isolated and controlled conditions, from such microbes can be the most suitable way of using them to enhance plant growth, without resulting in risk to plants and humans.…”
Section: Pgpm Derived Compounds For Mitigation Of Salinity Stressmentioning
confidence: 99%